Molecular footprint and pathways of DOM biotransformation in the Yangtze River - Guangrui Yang; Farong Chen; Songchol Kang; Jiaming Chen; Chu Zhao; Lize Meng; Xinyi Zhang; Jiayue Lu; Shuaidong Li; Zihao Bian; Jian Zhou; Qihao Jiang; et al. (Water Research, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Chlorocholine chloride delays progenitor Leydig cell differentiation via PI3K/AKT pathway activation in rats - Haoran Zhang; Yijia Li; Xiaoxia Wang; Chenping Kang; Qiong Zhang; Defeng Liu; Jiaming Mao; Qianqian Xiao; Weidong Hao (Toxicology, 2026)

Adaptive isoline interval optimization for precise contour segmentation and instance-level detection of Martian impact craters - Dong Chen; Fan Hu; Jiaming Na; Zhenxin Zhang; Zhen Cao; Liqiang Zhang; Zhizhong Kang; Jiju Poovvancheri; Norbert Pfeifer (Icarus, 2025)

Floodplain hydrodynamics and connectivity in a natural compound channel during unsteady flow events - Jiaming Liu; Yang Xiao; Saiyu Yuan; Taotao Zhang; Qingwei Lin; Kang Yuan; Ruiqi Wang; Carlo Gualtieri (Journal of Hydrology, 2025)

Corrigendum to “Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River” [Sci. Total Environ. 951 (2024) 175535] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2025)

Study on rockburst control of deep-buried tunnel by combining advanced stress release borehole and hydraulic fracturing - Jiaming Li; Shibin Tang; Tianjiao Li; Shuguang Zhang; Liexian Tang; Kang Sun (Tunnelling and Underground Space Technology, 2025)

GACraterNet: A collaborative geometry-attribute domain network for enhanced detection of Martian impact craters - Fan Hu; Dong Chen; Jiaming Na; Zhen Cao; Zhenxin Zhang; Liqiang Zhang; Zhizhong Kang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

SbSeI for high-efficient photocatalytic degradation of multiple pollutants - Kang Li; Yue Gao; Zhongxin Dong; Huibo Zhang; Xudong Fan; Lei Xu; Jie Huang; Feng Teng; Haibo Fan; Jiaming Song; Chunmei Zhang; Xuexia He; et al. (Environmental Research, 2024)

Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2024)

Development of a 3D point cloud reconstruction-based apple canopy liquid sedimentation model - Chongchong Chen; Yalan Jia; Jiaming Zhang; Linsen Yang; Yaxiong Wang; Feng Kang (Journal of Cleaner Production, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Effects of ultrasound-assisted emulsification and carboxymethyl cellulose addition on the rheological and microstructure properties of myofibrillar protein-soybean oil emulsion gel - Lei Zhou; Dacheng Kang; Jingyu Wang; Jiaming Cai; Lujuan Xing; Wangang Zhang (Food and Bioproducts Processing, 2024)

An image-based system for locating pruning points in apple trees using instance segmentation and RGB-D images - Siyuan Tong; Jiaming Zhang; Wenbin Li; Yaxiong Wang; Feng Kang (Biosystems Engineering, 2023)

Isolation and identification of a megalocytivirus strain (SKIV-TJ) from cultured spotted knifejaw (Oplegnathus punctatus) in China and its pathogenicity analysis - Jiaming Liao; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2023)

Extreme low-temperature events can alleviate micronutrient deficiencies while increasing potential health risks from heavy metals in rice - Min Kang; Xue Wang; Jiankun Chen; Qizhao Fang; Jiaming Liu; Liang Tang; Leilei Liu; Weixing Cao; Yan Zhu; Bing Liu (Environmental Pollution, 2023)

Establishment and characterization of a brain tissue cell line from spotted knifejaw ( Oplegnathus punctatus ) and its susceptibility to several fish viruses - Jiaming Liao; Xin Zhang; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Journal of Fish Diseases, 2023)
Cells are important in the study of virus isolation and identification, viral pathogenic mechanisms and antiviral immunity. The spotted knifejaw ( Oplegnathus punctatus ) is a significant farmed fish in China that has been greatly affected by diseases in recent years. In this study, a new cell line derived from the spotted knifejaw brain (SKB) was established and characterized. SKB cells multiplied well in Leibovitz's L‐15 medium supplemented with 10% fetal bovine serum at 28°C. Chromosome analysis revealed that modal chromosome number was 48 for SKB. SKB cells exhibit susceptibility to several fish viruses, such as a largemouth bass virus, red grouper nervous necrosis virus (RGNNV), infectious spleen and kidney necrosis virus (ISKNV), Singapore grouper iridovirus (SGIV) and spotted knifejaw iridovirus isolate (SKIV‐TJ), as shown by cytopathic effect and increased viral titers. Electron microscopy results showed that the cytoplasm contained a large number of vacuoles, and many virus particles existed at the edge of the vacuoles in RGNNV‐infected cells and numerous viral particles were scattered throughout the cytoplasm in both ISKNV‐ and SKIV‐TJ‐infected cells. These results suggest that SKB is an ideal tool for studying host–virus interactions and potential vaccine development.

Surfactant-induced photocatalytic performance enhancement of europium oxide nanoparticles - Yishuai Jing; Tianxin Kang; Peng Hu; Haibo Fan; Feng Teng; Xin Zhao; Jiaming Song (Process Safety and Environmental Protection, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Generation of reactive oxygen species through dissolved oxygen activation on defected porous carbon for efficient degradation of antibiotics - Jiaming Liu; Zhangwei Yao; Genping Qiu; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; Wenjing Yuan; Peihai Ju; Ruixi Lin; Hengcheng Zhou; et al. (Chemical Engineering Journal, 2023)

Differential patterns and assembly processes of bacterial communities from distinct microhabitats in a subtropical estuary - Kang Ma; Ze Ren; Jiaming Ma; Nannan Chen; Jingling Liu (Frontiers in Marine Science, 2022)
Estuarine ecosystems interconnect freshwater and marine environments, and comprise multiple highly dynamic and complex microhabitats. The resident microbiota in estuary is influenced by contrasting microenvironmental heterogeneity. However, the bacterial patterns and assembly processes in different microhabitats of estuarine ecosystem are not well studied. Here, we investigated the bacterial diversity, functions and community assembly mechanisms of mangrove soil, river sediment and overlying water in a subtropical estuary. Results showed that similar profiles of bacterial communities existed in the mangrove soil and river sediment and were dominated by Proteobacteria, Bacteroidetes and Acidobacteria. In terms of different microhabitats, the lowest alpha diversity of bacterial communities was found in overlying water and were dominated by Proteobacteria, Actinobacteria and Bacteroidetes. Meanwhile, the functional potential genes associated with carbon metabolisms were also substantially different in the three microhabitats. The relative abundance of genes connected to aerobic carbon respiration was significantly higher in overlying water than in the other two microhabitats. Bacterial communities in river sediments were enriched for genes associated with aerobic methane oxidation. The strong environmental heterogeneity of the three nearby microhabitats shaped the taxonomic and functional composition of the bacterial communities in estuarine ecosystem. Moreover, the plant rhizosphere effect increased the proportion of the dispersal limitation processes in mangrove soils compared to that in river sediments, while the overlying water was fluid and had less environmental selection processes compared to that in mangrove soil and river sediment. The bacterial communities in river sediment construct a more clustered network, while the overlying water network showed the highest complexity. Our findings reveal the differences of bacterial patterns and community assembly mechanisms in distinct microhabitats of estuarine ecosystems, and provide important insights for a comprehensive understanding of the mechanisms to maintain estuarine wetland conservation under environmental changes.

Study on mechanical properties and elasto-brittle-plastic constitutive model of hard brittle rock based on conventional triaxial test - Xinxin Fang; Han Tong; Jiaming Feng; Yanqiu Wang; Xiaowei Ni; Shaoyong Hou; Kang Bie (Arabian Journal of Geosciences, 2022)

Alleviation of atrazine toxicity to maize seedlings grown in soils with amendment of biochar derived from wheat under different temperatures - Yifan Wang; Yi Tang; Qun Jiang; Xinyuan Zhang; Weiling Xie; Ruizhen Li; Wenzhu Liu; Jiaming Kang; Ying Zhang (Environmental Science and Pollution Research, 2019)

The Association Between Myocardial Fibrosis and Depressed Capillary Density in Rat Model of Left Ventricular Hypertrophy - Ying Xiao; Yinjie Liu; Jiaming Liu; Y. James Kang (Cardiovascular Toxicology, 2018)

Safety Evaluation of Sevoflurane as Anesthetic Agent in Mouse Model of Myocardial Ischemic Infarction - Xiang Cheng; Jianglong Hou; Jiaming Liu; Xiaorong Sun; Qin Sheng; Pengfei Han; Y. James Kang (Cardiovascular Toxicology, 2017)